FAKTOR-FAKTOR YANG MELATARBELAKANGI KEPUTUSAN BELANJA ONLINE PADA APLIKASI E-COMMERCE - AFRILIANTI, NI KADEK DWI ARISYA; SUSILAWATI, MADE; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2022)
The existence of the COVID-19 Pandemic since 2020 has forced the central government to impose large-scale social restrictions (PSBB) in the various region in Indonesia. This restriction aims to minimize the spread of the COVID-19 virus, but this causes results in many people losing their jobs. This study uses confirmatory factor analysis to examine the factors behind online shopping decisions at stores in e-commerce applications. The results of this study aim to determine what factors are behind the decision of buyers to shop online in e-commerce applications. The research variable consists of eight dimensions: product, price, place, promotion, customer service, convenience, security, and trust, with 33 indicators. The sample in this study was the people of Denpasar City, totaling 232 respondents who had shopped online at least three times in the last six months. The results of the factor analysis obtained that it is true that there are eight factors behind online shopping decisions at shops in e-commerce applications by people in Denpasar City. These results can be considered for online entrepreneurs to increase sales results by sellers and as a reference by buyers in determining what can be regarded as in online shopping.